Digital Literacy and Civic Education in the Digital Era: A Bibliometric Analysis (2016–2025) - Anastasya Anastasya; Iqbal Arpannudin (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
This study aims to map digital literacy trends in civic education in the digital age through bibliometric analysis. Data were collected from the Scopus database for the period 2016–2025 by applying the PRISMA protocol, resulting in 123 relevant articles. The analysis was conducted using R Biblioshiny and VOSviewer software to trace publication trends, dominant keywords, research themes, and patterns of collaboration between authors and countries. The results showed a significant increase in publications after the COVID-19 pandemic, with the largest contributions coming from the United States and Indonesia. The main focus of the study included digital citizenship, civic education, and media literacy, accompanied by related issues such as disinformation, fake news, and digital ethics. This research provides a new contribution by strengthening the theory of digital citizenship education as a development of the conventional civic education theory. The integration of digital literacy will expand the theoretical framework of learning, especially in citizenship education based on critical digital literacy, which is the ability to reflectively assess information and participate ethically in the digital public sphere.